Pandangan Dunia Pengarang Terhadap Permasalahan Sosial dalam Novel Bumi dan Lukanya Remake Karya Ann - Ni Luh Ratna Ardiari; I Ketut Yarsama; I Made Sujaya (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research is a qualitative descriptive study that describes the structure and also the author's world view of social problems in the novel Bumi dan Lukanya Remake by Ann. The theory used in this research is the theory of genetic structuralism developed by Goldmann. The data collection methods and techniques used were library study methods and reading and note-taking techniques. The data source for this research uses the novel Bumi dan Lukanya Remake by Ann. Data analysis uses the dialectical method. The results of the analysis are presented using informal methods using descriptions as explanations. This research produces a structure that originates from relationships built from an imaginary environment, namely (1) familial relationships between characters, (2) friendly relationships between characters, and (3) love relationships between characters and the author's world view of social problems in the novel Bumi dan Lukanya Remake .